ENKULTURASI BUDAYA DAN PROSES PERKEMBANGAN MANUSIA - Ade Saputra; Aisyah Shinta Balkhis, Annisa Rahmawati, Gefira Adias Permata, Najla Alifah, Syfa Salsa Azahra (ADISAM PUBLISHER, 2024)
Indonesia, with its diverse cultures and ethnic groups, has tremendous cultural wealth. Enculturation, as a process of internalizing cultural values and norms, is key in shaping individual identity. This research aims to examine how the process of enculturation affects human development, particularly in the context of Indonesia's cultural diversity. This research is based on the importance of understanding enculturation in the context of individual development. Enculturation involves not only cognitive learning, but also the process of internalizing values that shape individual character and behavior. This process takes place from an early age and involves various socialization agents such as family, school and society. This research is expected to contribute to a deeper understanding of the relationship between enculturation and human development. The results of this study can be used as a basis for the development of educational and cultural programs that are more effective in preserving cultural values and forming a young generation with character